Assembling and Regulating of Transition Metal‐Based Heterophase Vanadates as Efficient Oxygen Evolution Catalysts. Issue 7 (5th December 2021) - Shao, Wenjie; Xiao, Mingjun; Yang, Chengdong; Cheng, Menghao; Cao, Sujiao; He, Chao; Zhou, Mi; Ma, Tian; Cheng, Chong; Li, Shuang
Abstract: Developing efficient, durable, and low‐cost earth‐abundant elements‐based oxygen evolution reaction (OER) catalysts by rapid and scalable strategies is of great importance for future sustainable electrochemical hydrogen production. The earth‐abundant high‐valency metals, especially vanadium, can modulate the electronic structure of 3 d metal oxides and oxyhydroxides and offer the active sites near‐optimal adsorption energies for OER intermediates. Here, the authors propose a facile assembling and regulating strategy to controllably synthesize a serial of transition metal (CoFe, NiFe, and NiCo)‐based vanadates for efficient OER catalysis. By tuning the reaction concentrations, NiFe‐based vanadates with different crystallinities can be facilely regulated, where the catalyst with moderate heterophase (mixed crystalline and amorphous structures) shows the best OER catalytic activity in terms of low overpotential (267 mV at the current density of 10 mA cm −2 ), low Tafel slope (38 mV per decade), and excellent long‐term durability in alkaline electrolyte, exceeding its noble metal‐based counterparts (RuO2 ) and most current existing OER catalysts. This work not only reports a facile and controllable method to synthesize a series of vanadates‐based catalysts with heterophase nanostructures for high‐performance OER catalysis, but also may expand the scope of designing cost‐effective transition metal‐based electrocatalysts for water splitting. Abstract : Transition metal‐based heterophase vanadates are assembled and regulated for efficient oxygen evolution electrocatalysis. The synthesized NiFe–VO x –0.5 with mixed crystallized and amorphous nanostructures exhibits excellent oxygen evolution catalytic activity (overpotential: 267 mV at 10 mA cm −2, Tafel slope: 38 mV per decade), and long‐term durability in alkaline electrolyte, which exceeds its counterparts and most current existing oxygen evolution catalysts.